Krukenberg tumor due to gastric cancer in pregnancy - Report of 2 cases - Esra Altan Erbilen; Sevgi Gökdoğan; Cihan İnan; Füsun Varol; Cenk Sayın (Hygeia Press di Corridori Marinella, 2022)
Krukenberg tumors (KTs) are 1-2% of all ovarian tumors, they are rare in pregnancy, and they have a poor prognosis since they are detected in advanced stages. We report 2 cases of KT in pregnancy. Bilateral giant solid adnexal masses were detected at the 25th gestational week in the 1st case and at the 14th gestational week in the 2nd case. Both of our patients had persistent nausea, vomiting, and abdominal pain. Salpingo-oophorectomy without gastrectomy was the procedure applied at the 25th and the 18th weeks in our cases, respectively. Chemotherapy was applied after the diagnosis of the KT. Preterm delivery, which is an expected complication in patients receiving chemotherapy during pregnancy, also occurred in our patients, and patients died 3 months and 5 months after the diagnosis, respectively. In conclusion, the adnexal region should be routinely checked during pregnancy. Cases with persistent gastrointestinal symptoms along with an adnexal mass should be evaluated with gastroscopy. The gestational week should be taken into account and a multidisciplinary approach should be applied.